2021
DOI: 10.1080/13639080.2021.1946494
|View full text |Cite
|
Sign up to set email alerts
|

A multi-institutional exploration of the social mobility potential of degree apprenticeships

Abstract: This mixed-method study at six universities asked degree apprentices about their trajectories into the apprenticeship, to better understand the social mobility potential of apprenticeships. The degree apprenticeship offers a route to a degree for apprentices, who are employees studying for a degree. As a new model, little is known about the apprentices: who they are, their journey towards this degree, and whether they fulfil the social mobility aspirations expressed by apprenticeship policymakers. Computing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Craftmanship is not a new concept. In the United Kingdom, there is a degree apprenticeship model and likely to give a new route to highly-paid work (Smith et al ., 2021). Fabian et al .…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Craftmanship is not a new concept. In the United Kingdom, there is a degree apprenticeship model and likely to give a new route to highly-paid work (Smith et al ., 2021). Fabian et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…In summary, several literature such as Evawoma-Enuku and Mgbor (2005), Donkor (2012), Ho (2016), Afolabi et al . (2017), Craig and Bewick (2017), Asiyanbola (2018), QAA (2019), Sambe (2019), Smith et al . (2021) and Osuizugbo et al .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Smith et al later surveyed apprentices at six institutions across Scotland and found that they came from all socio-economic backgrounds and included both those who had already worked in IT and those who were new to the sector. They identify the impact of employer selection as a key factor in social mobility and describe the apprenticeship as a "belated opportunity for social mobility" [32]. Finally, Smith et al also explore to what extent these new programs help to address the gender imbalance in computing.…”
Section: Related Workmentioning
confidence: 99%
“…Further, concerns have been raised that degree apprenticeships are less accessible to people from disadvantaged backgrounds, with only 17% of new starts drawn from such backgrounds in England in 2017/2018 (Battiston et al ., 2020). In terms of new hires, social mobility is not increasing (Smith et al , 2021; Cavaglia et al ., 2022). Mackay (2022) highlights the “middle class grab” (p. 208) for degree apprenticeships and calls on the government to incentivise employers to recruit with consideration for social mobility.…”
Section: Introductionmentioning
confidence: 99%